Poverty-Forests Linkages Toolkit : Overview and National Level Engagement - PROFOR (World Bank, Washington, DC, 2013)
Over the past few years there has been a growing interest in the role that forests play in supporting the poor, in reducing their vulnerability to economic and environmental shocks, and in reducing poverty itself. International workshops in Italy, Scotland, Finland and Germany have focused on the contribution of forests to livelihoods and the policies needed to strengthen that contribution. At the same time, Forestry Ministries, though they are now beginning to feel challenged to demonstrate the ways in which forests contribute to poverty reduction, are for the most part moving only slowly to collect new kinds of data to meet this challenge. There are two main reasons why the role of forests in poverty reduction has not so far been reflected in any significant way in either national level Poverty Reduction Strategy (PRS) processes or in national forest programs (NFPS). First, most countries have little data available to illustrate how forests contribute to the livelihoods of poor households. Second, the data that does exist rarely gets presented in ways that are meaningful to those designing PRSPs and NFPS. On the poverty side, there is a tendency to underestimate the contribution of forests and off farm natural resources in general, to livelihoods. On the forestry side, reporting is typically in terms of the physical resource (trees planted, forest cover improved, timber sold) rather than livelihoods, with the sole exception of recording the number of people formally employed in the forest sector. Such reporting sheds no light on the contributions made by forests to the lives of the poor. Their previous experience of data collection has not prepared them for this. The objective of the partnership was four-fold: first, to devise a rapid methodology for appraising forest-livelihood linkages from field exercises; second, to undertake more extended research through a series of case studies in six countries; and third, and most importantly, the objective was to devise ways by which locally gathered data could enrich national level and in due course national level processes such as PRSPs (Poverty Reduction Strategy Processes) and NFPS. Finally, the availability of this data would better equip countries for international country reporting on forests, and for participation in the international dialogue on forests. This toolkit is the key product from the partnership. It has been tested in Indonesia, Tanzania, Cameroon, Ghana, Madagascar and Uganda, with the help of external agencies. It is also worth noting that as the toolkit methodology is directed at strengthening the 'voice of the poor' in national policy debates it has relevance to other policy processes beyond poverty reduction.